2021
DOI: 10.3390/nu13072325
|View full text |Cite
|
Sign up to set email alerts
|

Small and Large Intestine (II): Inflammatory Bowel Disease, Short Bowel Syndrome, and Malignant Tumors of the Digestive Tract

Abstract: The small intestine is key in the digestion and absorption of macro and micronutrients. The large intestine is essential for the absorption of water, to allow adequate defecation, and to harbor intestinal microbiota, for which their nutritional role is as important as it is unknown. This article will describe the causes and consequences of malnutrition in patients with inflammatory bowel diseases, the importance of screening and replacement of micronutrient deficits, and the main indications for enteral and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 128 publications
0
7
0
Order By: Relevance
“…Several studies have suggested that patients with the L4 phenotype have a worse prognosis than those with other phenotypes, which manifests as an increased risk for complications, surgery, and further hospitalization ( 24 , 32 34 ). The small intestine is essential for the digestion and absorption of macro- and micronutrients ( 35 ). Intestinal cells impairment hampers the absorption of nutrients in the body ( 36 , 37 ), which is sufficient to explain the predisposition of L4-phenotype patients to malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that patients with the L4 phenotype have a worse prognosis than those with other phenotypes, which manifests as an increased risk for complications, surgery, and further hospitalization ( 24 , 32 34 ). The small intestine is essential for the digestion and absorption of macro- and micronutrients ( 35 ). Intestinal cells impairment hampers the absorption of nutrients in the body ( 36 , 37 ), which is sufficient to explain the predisposition of L4-phenotype patients to malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The largest digestive organ in the human body is the intestine, with digestion in the small intestine being the most important stage in the entire digestive process. 25 Intestinal barrier damage can lead to a dysregulation of intestinal homeostasis, along with increased intestinal permeability and leakage of harmful substances ( e.g. LPS), resulting in local and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Fish are useful models for gut‐related diseases (Thomson et al , 2012a,b; Kamareddine et al , 2020; Ber et al , 2021; Lee et al , 2021; Montoro‐Huguet et al , 2021). The discovery of fish CM indicates more differences between fish and mammal gut structures, which affects the comparative studies based on fish models.…”
Section: Discussionmentioning
confidence: 99%